The Digital Revolution in Chronic Care: Best Digital Health Apps for Chronic Disease Management - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The Digital Revolution in Chronic Care: Best Digital Health Apps for Chronic Disease Management The global burden of chronic diseases—such as diabetes, ...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation